1989
DOI: 10.1111/j.1749-6632.1989.tb25895.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of Vitamin A in Normal and Synchronized Seminiferous Tubulesa

Abstract: Vitamin A is clearly an important factor in spermatogenesis. Some of the new data on metabolism of retinoids in the testis has contributed to our understanding of the mechanism(s) involved in the action of vitamin A. It is probable that the requirement of the testis of vitamin A deficient rats for retinol but not retinoic acid involves access of the retinoids to various testicular compartments. Retinol may be required by germinal cells because of a requirement for esterification in order to be successfully tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 40 publications
6
112
1
1
Order By: Relevance
“…A slow, chronic, desquamation of immature germ represents another early feature of VAD in the Rbp4-null mutant mice. Loss of germ cell through desquamation has also been described in vitamin A-deficient rats (Unni et al, 1983;Griswold et al, 1989) as well as in mice lacking RAR␣ (Lufkin et al, 1993). These data underline a critical role of RA signalling in maintaining the cohesiveness of the seminiferous epithelium, which may be achieved either by controlling the permeability of Sertoli cell tight junctions (Unni et al, 1983;Huang et al, 1988), or the expression of cell adhesion molecules holding together Sertoli and germ cells (reviewed in Mruk and Cheng, 2004).…”
Section: Spermiation and Adhesion Of Germ Cells Are Highly Sensitive mentioning
confidence: 92%
“…A slow, chronic, desquamation of immature germ represents another early feature of VAD in the Rbp4-null mutant mice. Loss of germ cell through desquamation has also been described in vitamin A-deficient rats (Unni et al, 1983;Griswold et al, 1989) as well as in mice lacking RAR␣ (Lufkin et al, 1993). These data underline a critical role of RA signalling in maintaining the cohesiveness of the seminiferous epithelium, which may be achieved either by controlling the permeability of Sertoli cell tight junctions (Unni et al, 1983;Huang et al, 1988), or the expression of cell adhesion molecules holding together Sertoli and germ cells (reviewed in Mruk and Cheng, 2004).…”
Section: Spermiation and Adhesion Of Germ Cells Are Highly Sensitive mentioning
confidence: 92%
“…Studies have demonstrated that in VAD adult mice, all differentiated germ cells are lost from the seminiferous tubules and the only cells remaining are undifferentiated type A spermatogonia and Sertoli cells (Mitranond et al 1979, Van Pelt & de Rooij 1990. However, once these rats are administered vitamin A, normal spermatogenesis can be rescued (Morales & Griswold 1987, Griswold et al 1989. At first, studies demonstrated that normal spermatogenesis could only resume if vitamin A (retinol) was given to the deficient mice and that the same results were not observed upon Gonocyte and spermatogonia differentiation R141 RA administration (Ahluwalia & Bieri 1971, Huang et al 1983.…”
Section: Transitional Gonocyte Differentiation In Rodentsmentioning
confidence: 96%
“…The abnormalities that occur at specific stages of spermatogenesis as a result of vitamin A deficiency (VAD) have been extensively studied, particularly in the rat de Rooij et al, 1994;Eskild and Hansson, 1994;Griswold et al, 1989). Although the morphological changes in spermatogenesis upon VAD have been well documented, the molecular mechanisms underlying these changes are still largely unknown and are likely to be complex.…”
Section: Introductionmentioning
confidence: 99%